High-adhesion damp-heat-resistant yellowing-resistant photovoltaic adhesive and preparation method thereof

By introducing urea-bonded heterocyclic and alicyclic structures into photovoltaic adhesives, combined with appropriate diluents and additives, the weather resistance of photovoltaic adhesives in humid and heat environments is solved, and high adhesion and yellowing resistance are achieved. It is suitable for use Stable connection and protection of photovoltaic modules.

CN119307218AActive Publication Date: 2025-01-14SUZHOU HEBANG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411576788.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-14
Estimated Expiration
2044-11-06

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure FDA0005121984390000011
    Figure FDA0005121984390000011
Patent Text Reader

Abstract

The invention discloses a high-adhesion damp-heat-resistant and yellowing-resistant photovoltaic adhesive and a preparation method thereof. The high-adhesion damp-heat-resistant and yellowing-resistant photovoltaic adhesive is prepared from the following raw material components in parts by weight: 40-60 parts of light-cured acrylate, 34-44 parts of a reactive diluent, 0.5-4 parts of a photoinitiator, 0.05-3.5 parts of a first polymerization inhibitor and 1-6 parts of an auxiliary agent, the structure of the light-cured acrylate is as follows: A-(B-C) x, in which A is a heterocyclic compound containing a urea bond; b is an alicyclic diisocyanate monomer; c is a hydroxyl-containing acrylic acid derivative, and x is from 1 to 5. The photovoltaic adhesive disclosed by the invention can meet the general requirements of photovoltaic adhesives, has high adhesive force, damp-heat resistance, aging resistance and yellowing resistance, and is matched with a low-temperature tin-coated welding strip, so that the welding strip and a battery piece realize dual fixation, the stripping force between the welding strip and the battery piece is greatly improved, meanwhile, traditional infrared heating welding is replaced, and the production cost is reduced for lightening and thinning the battery piece at the assembly end. And the realizability is provided by reducing the cost and the energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a photovoltaic adhesive with high adhesion, resistance to moisture and heat, and resistance to yellowing, and a preparation method thereof. Background Art

[0002] With the rapid development of social economy and population, people's demand for energy is also increasing. As a new energy source, solar energy mainly comes from sunlight radiated by the sun, with huge reserves and friendly to the ecological environment. Photovoltaic power generation is a technology that uses the photovoltaic effect of the semiconductor interface to convert light energy into electrical energy. When used in industry, solar cells need to be connected in series or in parallel to form a module to obtain a higher output voltage. Photovoltaic modules are the smallest unit of photovoltaic power generation.

[0003] In the production process of photovoltaic modules, how to use single solar cells in series or in parallel not only affects the photoelectric conversion efficiency of photovoltaic modules, but also affects the difficulty of the production process. Series connection can increase the voltage of the entire battery array, while parallel connection can increase the current. As a key material for connecting cells, the performance of photovoltaic ribbon has a direct impact on the efficiency and life of the module. The use of photovoltaic ribbon connection has always been considered one of the most mature photovoltaic module packaging methods. In order to reduce silver consumption, increase power and improve yield, the main grid is eliminated in the existing cell link, and the current is derived from the component link using the ribbon. Photovoltaic ribbon dispensing technology is a key link in the production of photovoltaic modules. This process includes first welding the ribbon to the cell, then dispensing the ribbon to further stick it to the cell, and finally laminating and alloying. This solution is different from the solution of only dispensing and laminating because it requires welding, welding to achieve preliminary fixation, and dispensing further fixation. Since high temperatures are used in the welding process, adhesives that can withstand high temperatures and have high bonding strength are required in the dispensing process. This ensures that the connection between the solder ribbon and the battery cell is both firm and reliable.

[0004] Since solar cells are thin, brittle, and easily oxidized, they are easily permanently damaged when exposed to air, rain, and other natural environments. Therefore, photovoltaic adhesives are used to connect and seal photovoltaic modules. In addition to having good bonding strength, they are also required to have good resistance to ultraviolet exposure, yellowing, humidity, heat, and aging to meet the requirements of the use environment. However, the performance of photovoltaic adhesives currently available on the market is still difficult to meet the use requirements. Patent CN117384580A discloses a highly thixotropic, high temperature and yellowing resistant photovoltaic solder tape UV glue, comprising the following components in parts by mass: oligomer: 40-60 parts, active monomer: 30-40 parts, modified mixed powder: 1-5 parts, surface photoinitiator: 1-5 parts, deep photoinitiator: 0.5-1 part; the modified mixed powder is added to the UV glue formula system, and the unique rheological properties of the mixed powder are utilized to prevent the glue from spreading before curing, thereby avoiding large-scale contamination of the battery cell. The mixed powder of the UV glue contains boron nitride with high heat transfer efficiency, which can quickly transfer heat and avoid the main body of the UV glue from being too high, thereby improving the temperature resistance of the UV glue, thereby ensuring that the component can resist the high temperature problem caused by short circuit for a short time, but the patent does not disclose the bonding strength and moisture and heat resistance of the joint.

[0005] Therefore, the development of photovoltaic adhesives with high adhesion, resistance to moisture and heat, resistance to aging, and resistance to yellowing remains an urgent problem to be solved. Summary of the invention

[0006] To solve the above problems, the present invention provides a photovoltaic adhesive with high adhesion, moisture and heat resistance, and yellowing resistance, and a preparation method thereof. By changing the type of the main resin and using different components in combination, the problem that the prior art cannot simultaneously achieve the requirements of high adhesion, moisture and heat resistance, aging resistance, and yellowing resistance can be overcome.

[0007] Specifically, the following technical solutions are provided:

[0008] The first aspect of the present invention provides a photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance, characterized in that it comprises the following raw material components in parts by weight: 40 to 60 parts of photocurable acrylate, 34 to 44 parts of reactive diluent, 0.5 to 4 parts of photoinitiator, 0.05 to 3.5 parts of first inhibitor and 1 to 6 parts of auxiliary agent; the photocurable acrylate has a structure as shown in general formula (I):

[0009] A-(BC) x (Ⅰ)

[0010] Wherein, A is a heterocyclic compound containing a urea bond; B is an alicyclic diisocyanate monomer; C is a hydroxyl-containing acrylic acid derivative, and x is from 1 to 5.

[0011] To solve the defects of solar cells such as thinness, brittleness, and easy oxidation, it is easy to cause permanent damage when exposed to natural environments such as air and rain; photovoltaic adhesives need to be resistant to high temperatures when using dispensing and welding strips at the same time. The present invention provides a photovoltaic adhesive with high adhesion, moisture resistance, and yellowing resistance, with homemade photocurable acrylate as the main resin component, and the resin structure is designed to be multi-functional, so as to ensure the bonding performance and strength of the photocurable acrylate composition after curing. However, if the urea-bonded heterocyclic compound with too much functionality is only suitable for modification with acrylic resin, it will have poor toughness due to its low molecular weight, and shrinkage and thermal expansion after curing are relatively large, thereby affecting its moisture resistance. The present invention can improve the toughness of the photocurable acrylate and enhance the strength after curing by introducing an alicyclic structure. The modified photocurable acrylate can simultaneously have a urea-bonded heterocyclic structure and an alicyclic structure to achieve better moisture resistance and stronger curing strength.

[0012] Furthermore, in the general formula of the photocurable acrylate, A is selected from the following formula

[0013] A kind of

[0014] Here, n is from 1 to 4.

[0015] Further, the alicyclic diisocyanate monomer is selected from cyclopentylene-1,3-diisocyanate, cyclohexylene-1,4-diisocyanate, cyclohexylene-1,2-diisocyanate, dicyclohexylmethane diisocyanate (HMDI), 1-isocyanato-2-diisocyanatomethylcyclopentane, 1-isocyanato-3-isocyanato-methyl-3,5,5-trimethylcyclohexane (isophorone diisocyanate or IPDI), bis-(4-isocyanatocyclohexyl)-methane, 2,4-dicyclohexylmethane diisocyanate, 1,3- or 1,4-bis-(isocyanatomethyl)-cyclohexane, bis-(4-isocyanato-3-methylcyclohexyl)-methane, 1-isocyanato-1-methyl-4(3)-isocyanatomethylcyclohexane, 2,4- or 2,6-hexahydrotoluene diisocyanate or more thereof.

[0016] Furthermore, the alicyclic diisocyanate monomer is 1-isocyanato 3-isocyanato-methyl-3,5,5-trimethylcyclohexane (isophorone diisocyanate or IPDI) or dicyclohexylmethane diisocyanate (HMDI).

[0017] Furthermore, the hydroxyl-containing acrylic acid derivative is selected from one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, hydroxyethyl acrylamide, hydroxypropyl methacrylate and hydroxypropyl acrylate.

[0018] Furthermore, the hydroxyl-containing acrylic acid derivative is hydroxyethyl acrylate (HEA) or hydroxyethyl methacrylate (HEMA).

[0019] Further, the active diluent is selected from one or more of isobornyl acrylate, isobornyl methacrylate, isooctyl acrylate, isooctyl methacrylate, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, trimethylolpropane triacrylate, 2-phenoxyethyl acrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, n-butyl acrylate, isodecyl acrylate, lauric acid acrylate, cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, 4-tert-butylcyclohexyl acrylate, dicyclopentenyl acrylate, pentaerythritol tetraacrylate, and cyclotrimethylolpropane formal acrylate.

[0020] Furthermore, the active diluent is a combination of isobornyl acrylate and cyclotrimethylolpropane formal acrylate.

[0021] Further, the photoinitiator is selected from one or more of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, 2,2-dimethoxy-2-phenylacetophenone, methyl benzoylformate, isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxycyclohexylphenyl ketone.

[0022] Furthermore, the photoinitiator is a combination of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and 1-hydroxycyclohexylphenyl ketone.

[0023] Furthermore, the auxiliary agent is selected from one or more of a stabilizer, a diluent, an antioxidant, an adhesion promoter, a coupling agent, a defoamer, a leveling agent, a wetting agent, a leveling agent, a toughening agent, a flame retardant, a pigment and a filler.

[0024] The second aspect of the present invention provides a method for preparing the photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as described in the first aspect, characterized in that it comprises the following steps:

[0025] S1. In a light-proof condition, a diisocyanate monomer, a first catalyst, an antioxidant, and a second polymerization inhibitor are mixed, and a hydroxyl-containing acrylic acid derivative is added dropwise at 40 to 50° C. When the NCO content in the reaction reaches 50% of the initial theoretical value, an intermediate product 1 is obtained;

[0026] S2, under light-proof conditions, mixing a urea-bond heterocyclic compound and a second catalyst, raising the temperature to 60-80° C., adding dropwise the intermediate product 1, and reacting until the NCO mass content reaches 0.1%, thereby obtaining the light-curable acrylate;

[0027] S3. Mix the photocurable acrylate, reactive diluent, photoinitiator, first polymerization inhibitor and auxiliary agent, and stir for 1 to 5 hours under vacuum degree -0.005 MPa to -0.2 MPa and temperature 20 to 40° C. to obtain a photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance.

[0028] Furthermore, in step S1, the molar ratio of the diisocyanate monomer to the hydroxyl-containing acrylic derivative is 1:(1-1.3), such as 1:1, 1:1.1, 1:1.2, 1:1.3, etc., including but not limited to the ratios listed above.

[0029] Furthermore, in step S2, the molar ratio of the alcoholic hydroxyl group in the urea-containing heterocyclic compound to the intermediate product 1 is (0.8-1):1; for example, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, etc., including but not limited to the ratios listed above.

[0030] Furthermore, the mass ratio of the photocurable acrylate to the diluent is 1:(0.65-0.9); for example, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, etc., including but not limited to the ratios listed above.

[0031] Furthermore, the first and second catalysts are respectively selected from one or more of organic tin, organic bismuth, organic zinc, organic cobalt and organic base catalysts.

[0032] Furthermore, the first and second catalysts are both dibutyltin dilaurate.

[0033] Further, the antioxidant is selected from one or more of 2,6-di-tert-butyl-4-methylphenol, 4,4'-thiobis(6-tert-butyl-3-methylphenol), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, triphenyl phosphite and trinonylphenyl phosphite.

[0034] Furthermore, the antioxidant is 2,6-di-tert-butyl-4-methylphenol.

[0035] Furthermore, the first polymerization inhibitor and the second polymerization inhibitor are independently selected from one or more of p-hydroxyanisole, p-benzoquinone, hydroquinone, 2-tert-butylhydroquinone, 2,5-di-tert-butylhydroquinone, phenothiazine and naphthoquinone.

[0036] Furthermore, the first polymerization inhibitor and the second polymerization inhibitor are both hydroquinone.

[0037] Beneficial effects of the present invention:

[0038] The present invention prepares a photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance. On the basis of achieving light curing, a urea bond ring structure is introduced into the structure, which provides a structural skeleton that can be extended to multiple functionalities for the preparation of the main resin light-curing acrylate in the photovoltaic adhesive formula; and the urea ring structure has a stable structure and a large urea bond dissociation energy, which can improve the excellent heat resistance; since the light-curing acrylate contains a large number of amide bonds, the bonding performance of the photovoltaic adhesive cured product can be improved; the two ends of the alicyclic group provide good mechanical strength for the main resin and are not prone to yellowing like the benzene ring.

[0039] The alicyclic structure forms a tight and rigid molecular structure in the molecule, which improves the mechanical strength, heat stability and weather resistance of the cured photovoltaic adhesive. Because it is not like adhesives containing aromatic ring structures, the methyl group substituted on the aromatic ring is easily oxidized by complex factors such as light and heat in the environment to form a "quinone" structure that is prone to yellowing, the cured photovoltaic adhesive has excellent yellowing resistance.

[0040] Since photocurable acrylate contains a large number of carbamate bonds, it can form hydrogen bonds with polymer chains, so that the photovoltaic adhesive has excellent bonding properties after curing; and the synergistic effect with the cyclic urea bonds and alicyclic rings in the structure can obtain a photovoltaic adhesive cured product with a compact structure, good heat resistance and adhesion, which improves the reliability of photovoltaic modules in hot and humid environments.

[0041] The present invention prepares a photovoltaic adhesive with high adhesion, moisture and heat resistance and yellowing resistance. After formula screening, it can meet the general requirements of photovoltaic adhesives, has high adhesion, moisture and heat resistance, aging resistance, and yellowing resistance, and is matched with a low-temperature tin-coated solder strip, so that the solder strip and the battery cell are doubly fixed, greatly improving the peeling force between the two, and at the same time replacing traditional infrared heating welding, providing feasibility for thinning the battery cell at the component end and reducing costs and energy. DETAILED DESCRIPTION

[0042] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0043] The raw materials and sources used in the following examples and comparative examples are as follows:

[0044] Dibutyltin dilaurate (DBTDL), selected from McLean, brand name DBTDL; isophorone diisocyanate (IPDI), selected from Wanhua Chemical, brand name IPDI; dicyclohexylmethane diisocyanate (HMDI), selected from Wanhua Chemical, brand: HMDI; hydroxyethyl acrylate (HEA), selected from McLean, brand name HEA; hydroxyethyl methacrylate (HEMA), selected from Wanhua Chemical, brand name HEMA; 2,6-di-tert-butyl-4-methylphenol, selected from Shanghai Ronghe Chemical; hydroquinone, selected from Eastman, USA, brand name HQ; tetrakis (2-hydroxymethyl) glycoluril, selected from Siguo Chemical, brand name TH-G; tris (2-hydroxyethyl) isocyanurate, selected from Titan, brand name THMP; isobornyl acrylate, selected from Changxing, Taiwan, China, brand name EM214; cyclotrimethylolpropane methyl acrylate, selected from Sartomer, brand name SR351NS; 1-hydroxycyclohexyl phenyl ketone, selected from Omnirad184, brand name IGM; (2, 4,6-trimethylbenzoyl)diphenylphosphine oxide, selected from Jiuri New Materials, brand RCure-1108; silane coupling agent, selected from Momentive of the United States, brand SilquestA-187; fumed silica, selected from Wacker of Germany, brand H18; polyester acrylate, selected from Sartomer, brand CN704; epoxy acrylate, selected from Sartomer, brand CNUVE151; polyether modified polyurethane acrylate, selected from Changxing of Taiwan, China, brand 615-100; fumed silica, selected from Sartomer, brand CNUVE151.

[0045] Example 1

[0046] (1) In a three-necked flask with a thermometer, 100 g of IPDI, 1 g of catalyst DBTDL, 0.01 g of di-tert-butyl-4-methylphenol and 0.005 g of hydroquinone were added under light-proof conditions, and 53 g of HEA was added dropwise at 40° C. The NCO group concentration was continuously monitored during the reaction, and when it reached 50% of the initial theoretical value, the product IPDI-HEA was obtained.

[0047] (2) In a three-necked flask equipped with a thermometer, 29 g of tetrakis(2-hydroxymethyl)glycoluril and 1 g of catalyst DBTDL were added under light-proof conditions. The temperature was raised and maintained at 60° C., and the product IPDI-HEA in step 1 was added dropwise. The NCO content was tested every 30 minutes. When the NCO mass content was 0.1%, heating was stopped to obtain the final photocurable acrylate A.

[0048] (3) Add 49 parts of the photocurable acrylate A obtained in step (2), 20 parts of isobornyl acrylate, 20 parts of cyclotrimethylolpropane methyl acrylate, 0.5 parts of 1-hydroxycyclohexyl phenyl ketone, 1.5 parts of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 1.5 parts of 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, 0.15 parts of hydroquinone, and auxiliary agents (1.5 parts of silane coupling agent and 2 parts of fumed silica) into a reaction kettle by weight, and stir for 3 hours under vacuum degree -0.1 MPa and temperature of 25°C to obtain a photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance.

[0049] Example 2

[0050] The difference between this embodiment and embodiment 1 is that the contents of the following components are different:

[0051] 42 parts of light-curing acrylate A, 17 parts of isobornyl acrylate, and 17 parts of cyclotrimethylolpropane formal acrylate, and the other steps remain unchanged.

[0052] Example 3

[0053] The difference between this embodiment and embodiment 1 is that the contents of the following components are different:

[0054] 46 parts of light-curing acrylate A, 18 parts of isobornyl acrylate, and 18 parts of cyclotrimethylolpropane formal acrylate, and the other steps remain unchanged.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that the contents of the following components are different:

[0057] 56 parts of light-curing acrylate A, 21 parts of isobornyl acrylate, and 21 parts of cyclotrimethylolpropane formal acrylate, and the other steps remain unchanged.

[0058] Example 5

[0059] The difference between this embodiment and embodiment 1 is that the contents of the following components are different:

[0060] 59 parts of light-curing acrylate A, 22 parts of isobornyl acrylate, and 22 parts of cyclotrimethylolpropane formal acrylate, and the other steps remain unchanged.

[0061] Example 6

[0062] The difference between this embodiment and embodiment 1 is that the contents of the following components are different:

[0063] 17 parts of isobornyl acrylate and 18 parts of cyclotrimethylolpropane formal acrylate, and the other steps remain unchanged.

[0064] Example 7

[0065] The difference between this embodiment and embodiment 1 is that the contents of the following components are different:

[0066] 23 parts of isobornyl acrylate and 22 parts of cyclotrimethylolpropane formal acrylate, and other steps remain unchanged.

[0067] Example 8

[0068] (1) In a three-necked flask equipped with a thermometer, 100 g of HMDI, 1 g of catalyst DBTDL, 0.01 g of di-tert-butyl-4-methylphenol and 0.005 g of hydroquinone were added under light-proof conditions, and 64 g of HEMA was added dropwise at 50° C. The NCO group concentration was continuously monitored during the reaction, and when it reached 50% of the initial theoretical value, the product HMDI-HEMA was obtained.

[0069] (2) In a three-necked flask equipped with a thermometer, 26.6 g of tris(2-hydroxyethyl)isocyanurate and 1 g of catalyst DBTDL were added under light-proof conditions. The temperature was raised and maintained at 80° C., and the product HMDI-HEMA in step 1 was added dropwise. The NCO content was tested every 30 minutes. When the NCO mass content was 0.1%, heating was stopped to obtain the final photocurable acrylate B.

[0070] (3) Add 49 parts of the photocurable acrylate B obtained in step (2), 20 parts of isobornyl acrylate, 20 parts of cyclotrimethylolpropane methyl acrylate, 0.5 parts of 1-hydroxycyclohexyl phenyl ketone, 1.5 parts of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 1.5 parts of 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, 0.15 parts of hydroquinone, and auxiliary agents (1.5 parts of silane coupling agent and 2 parts of fumed silica) into a reaction kettle by weight, and stir for 5 hours under vacuum degree -0.2 MPa and temperature 40°C to obtain a photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance.

[0071] Example 9

[0072] The difference between this embodiment and embodiment 8 is that the contents of the following components are different:

[0073] 42 parts of light-curing acrylate B, 17 parts of isobornyl acrylate, and 17 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0074] Example 10

[0075] The difference between this embodiment and embodiment 8 is that the contents of the following components are different:

[0076] 46 parts of light-curing acrylate B, 18 parts of isobornyl acrylate, and 18 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0077] Embodiment 11

[0078] The difference between this embodiment and embodiment 8 is that the contents of the following components are different:

[0079] 56 parts of light-curing acrylate B, 21 parts of isobornyl acrylate, and 21 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0080] Example 12

[0081] The difference between this embodiment and embodiment 8 is that the contents of the following components are different:

[0082] 59 parts of light-curing acrylate B, 22 parts of isobornyl acrylate, and 22 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0083] Comparative Example 1

[0084] 49 parts of polyester acrylate, 20 parts of isobornyl acrylate, 20 parts of cyclotrimethylolpropane methyl acrylate, 0.5 parts of 1-hydroxycyclohexyl phenyl ketone, 1.5 parts of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 1.5 parts of 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, 0.15 parts of hydroquinone and auxiliary agents (1.5 parts of silane coupling agent and 2 parts of fumed silica) were added into a reactor by weight, and stirred for 3 hours under vacuum degree -0.1 MPa and temperature 25°C to obtain a photovoltaic adhesive.

[0085] Comparative Example 2

[0086] 49 parts of epoxy acrylate, 20 parts of isobornyl acrylate, 20 parts of cyclotrimethylolpropane methyl acrylate, 0.5 parts of 1-hydroxycyclohexyl phenyl ketone, 1.5 parts of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 1.5 parts of 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, 0.15 parts of hydroquinone and auxiliary agents (1.5 parts of silane coupling agent and 2 parts of fumed silica) were added into a reactor by weight, and stirred for 3 hours under vacuum degree -0.1 MPa and temperature of 25°C to obtain a photovoltaic adhesive.

[0087] Comparative Example 3

[0088] 49 parts of polyether modified polyurethane acrylate, 20 parts of isobornyl acrylate, 20 parts of cyclotrimethylolpropane formal acrylate, 0.5 parts of 1-hydroxycyclohexyl phenyl ketone, 1.5 parts of (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 1.5 parts of 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, 0.15 parts of hydroquinone and auxiliary agents (1.5 parts of silane coupling agent and 2 parts of fumed silica) were added into a reactor by weight, and stirred for 3 hours under vacuum degree -0.1 MPa and temperature of 25°C to obtain a photovoltaic adhesive.

[0089] Comparative Example 4

[0090] The difference between this comparative example and Example 1 is that the contents of the following components are different:

[0091] 65 parts of light-curing acrylate A, 22 parts of isobornyl acrylate, and 22 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0092] Comparative Example 5

[0093] The difference between this comparative example and Example 1 is that the contents of the following components are different:

[0094] 33 parts of light-curing acrylate A, 18 parts of isobornyl acrylate, and 18 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0095] Comparative Example 6

[0096] The difference between this comparative example and Example 8 is that the contents of the following components are different:

[0097] 65 parts of light-curing acrylate B, 22 parts of isobornyl acrylate, and 22 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0098] Comparative Example 7

[0099] The difference between this comparative example and Example 8 is that the contents of the following components are different:

[0100] 33 parts of light-curing acrylate B, 18 parts of isobornyl acrylate, and 18 parts of cyclotrimethylolpropane formal acrylate. Other steps remain unchanged.

[0101] Test Case

[0102] The shear strength and tensile strength of the products prepared in the examples and comparative examples were tested for performance.

[0103] (1) Tensile shear strength

[0104] The surfaces of the glass substrate and the aluminum substrate were wiped with ethanol. After the ethanol evaporated completely, a 0.2 mm aluminum foil tape was pasted on one end of the substrate. The resin composition obtained in the above embodiment and comparative example was applied to one end of the glass substrate to ensure that the resin composition was evenly applied on the bonding part. Then, the two substrates were overlapped and clamped with a transparent plastic clip. The sample was placed under an ultraviolet light source (365 nm, 300 mW / cm 2 ) Radiation curing for 10 seconds, then take out after full curing; The tensile shear strength test adopts GB / T7124-2008 standard, and the tensile shear strength test is carried out on an electronic tensile testing machine, the test temperature is 25°C, and the overlap area is 312.5mm 2 , the test rate is 5mm / min.

[0105] (2) Tensile shear strength after double 85

[0106] The tensile shear strength samples of the UV-cured glass-aluminum substrate were placed in a high temperature and high humidity test chamber, and the tensile shear strength was tested after standing for 200 hours at 85°C and 85% relative humidity according to GB / T 5170-2016 standard. The tensile shear strength test was carried out on an electronic tensile testing machine using GB / T 7124-2008 standard, with a test temperature of 25°C and an overlap area of ​​312.5mm 2 , the test speed is 5mm / min.

[0107] (3) Tensile shear strength after high temperature aging

[0108] The tensile shear strength samples of the UV-cured glass-aluminum substrate were placed in a high temperature and high humidity test chamber, and the tensile shear strength was tested after standing for 3 hours at 200°C according to GB / T 5170.2-2008 standard. The tensile shear strength test was carried out on an electronic tensile testing machine using GB / T 7124-2008 standard, with a test temperature of 25°C and an overlap area of ​​312.5mm. 2 , the test speed is 5mm / min.

[0109] (4) Yellowing difference before aging and after high temperature aging

[0110] The resin compositions obtained in the above examples and comparative examples were cast in a transparent plastic mold with a diameter of 5 cm, and then the samples were placed in an ultraviolet light source (365 nm, 300 mW / cm 2 ) Radiation cure for 10 seconds, then take out after full curing, and after demoulding, let it stand at 200°C for 3 hours according to GB / T5170.2-2008 standard, and use a colorimeter to test the yellowing value ΔYI before and after high temperature.

[0111] The performance test results of the products obtained in the embodiments and comparative examples are shown in Table 1:

[0112] Table 1

[0113]

[0114] Combined with the data in Table 1, by comparing Comparative Example 2 with Examples 1-12, it can be seen that the high-adhesion, moisture-resistant, heat-resistant and yellowing-resistant photovoltaic adhesives prepared in the present application can reach the initial tensile shear strength of the adhesive prepared from the commercially available acrylic resin containing a benzene ring structure, the tensile shear strength after double 85 that is close to it, and the tensile shear strength after high-temperature aging. However, since the photocurable acrylic structure prepared by the present invention does not contain a benzene ring structure, the photovoltaic adhesive protected by the present invention has good yellowing resistance and excellent mechanical properties and high moisture and heat resistance.

[0115] From the comparison between Example 1 and Comparative Example 1, it can be seen that the commonly used commercially available polyester photocurable resin, when used as the main resin of photovoltaic adhesive, has high initial tensile shear strength and good yellowing resistance, but its ester bond is easily hydrolyzed, so its moisture and heat resistance is poor. Although the polyester-modified polyurethane resin contains more ester bonds and can provide excellent initial tensile shear strength, the weather resistance requirements in the photovoltaic field have always restricted its development in this field.

[0116] From the comparison between Example 1 and Comparative Example 3, it can be seen that when the commonly used commercially available polyether-modified polyurethane acrylate is used as the main resin of the photovoltaic adhesive, although it has a high initial tensile shear strength, its moisture and heat resistance and yellowing resistance are poor. This is because the polyether chain segments are exposed to ultraviolet light and high temperature for a long time, which will accelerate the oxidation reaction of the polyether material and speed up its yellowing; it may even gradually undergo an oxidation reaction to form oxidation products, resulting in yellowing.

[0117] By comparing Examples 4-7 and 8-10 with Comparative Example 4-7, it can be seen that when the content of the prepared photocurable acrylate increases, due to the increase in the molecular weight of the resin composition, too many urethane bonds will affect the yellowing resistance of the cured product; when the content of the prepared photocurable acrylate decreases, the diluent content increases, and the corresponding main resin that can provide strength is reduced, resulting in reduced mechanical properties of the cured product, while too much small molecule diluent will lead to excessive crosslinking density and reduced adhesion of the cured product.

[0118] By comparing Examples 1-5 and 8-12, it can be seen that the photocurable acrylate A prepared in the present application has better properties than the photocurable acrylate B, because the curing resin A has more active functional groups, which makes the cross-linking structure of the cured product tighter, and thus has better moisture and heat resistance.

[0119] In summary, the use of the prepared photocurable acrylate as the main resin of photovoltaic adhesive with a diluent, and with suitable catalysts and inhibitors, additives, and fillers can meet the requirements of the photovoltaic adhesive field for high adhesion, moisture and heat resistance, aging resistance, and yellowing resistance, and has a high use value.

[0120] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A photovoltaic adhesive with high adhesion, heat resistance and yellowing resistance, characterized in that: The invention comprises the following raw material components in parts by weight: 40 to 60 parts of photocurable acrylate, 34 to 44 parts of reactive diluent, 0.5 to 4 parts of photoinitiator, 0.05 to 3.5 parts of first inhibitor and 1 to 6 parts of auxiliary agent; the photocurable acrylate has a structure as shown in the general formula (I): A-(B-C) x (Ⅰ) Wherein, A is a heterocyclic compound containing a urea bond; B is an alicyclic diisocyanate monomer; C is a hydroxyl-containing acrylic acid derivative, and x is from 1 to 5.

2. The photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 1, characterized in that: In the general formula of the photocurable acrylate, A is selected from the formula A kind of Here, n is from 1 to 4.

3. The photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 1, characterized in that: The alicyclic diisocyanate monomer is selected from cyclopentylene-1,3-diisocyanate, cyclohexylene-1,4-diisocyanate, cyclohexylene-1,2-diisocyanate, 4,4′-dicyclohexylmethane diisocyanate (HMDI), 1-isocyanato-2-diisocyanatomethylcyclopentane, 1-isocyanato-3-isocyanato-methyl-3,5,5-trimethylcyclohexane (isophorone diisocyanate) or IPDI), bis-(4-isocyanatocyclohexyl)-methane, 2,4-dicyclohexylmethane diisocyanate, 1,3- or 1,4-bis-(isocyanatomethyl)-cyclohexane, bis-(4-isocyanato-3-methylcyclohexyl)-methane, 1-isocyanato-1-methyl-4(3)-isocyanatomethylcyclohexane, 2,4- or 2,6-hexahydrotoluene diisocyanate; The hydroxyl-containing acrylic acid derivative is selected from one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, hydroxyethyl acrylamide, hydroxypropyl methacrylate and hydroxypropyl acrylate.

4. The photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 1, characterized in that: The active diluent is selected from one or more of isobornyl acrylate, isobornyl methacrylate, isooctyl acrylate, isooctyl methacrylate, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, trimethylolpropane triacrylate, 2-phenoxyethyl acrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, 1,4-butanediol diacrylate, n-butyl acrylate, isodecyl acrylate, lauric acid acrylate, cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, 4-tert-butylcyclohexyl acrylate, dicyclopentenyl acrylate, pentaerythritol tetraacrylate, and cyclotrimethylolpropane formal acrylate.

5. The photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 1, characterized in that: The photoinitiator is selected from one or more of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone, 2,2-dimethoxy-2-phenylacetophenone, methyl benzoylformate, isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone and 1-hydroxycyclohexylphenyl ketone.

6. The photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 1, characterized in that: The auxiliary agent is selected from one or more of a stabilizer, a diluent, an antioxidant, an adhesion promoter, a coupling agent, a defoamer, a leveling agent, a wetting agent, a leveling agent, a toughening agent, a flame retardant, a pigment and a filler.

7. A method for preparing the photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance according to any one of claims 1 to 6, characterized in that: The steps include: S1. In a light-proof condition, a diisocyanate monomer, a first catalyst, an antioxidant, and a second polymerization inhibitor are mixed, and a hydroxyl-containing acrylic acid derivative is added dropwise at 40 to 50° C. When the NCO content in the reaction reaches 50% of the initial theoretical value, an intermediate product 1 is obtained; S2, under light-proof conditions, mixing a urea-bond heterocyclic compound and a second catalyst, raising the temperature to 60-80° C., adding dropwise the intermediate product 1, and reacting until the NCO mass content reaches 0.1%, thereby obtaining the light-curable acrylate; S3. Mix the photocurable acrylate, reactive diluent, photoinitiator, first polymerization inhibitor and auxiliary agent, and stir for 1 to 5 hours under vacuum degree -0.005 MPa to -0.2 MPa and temperature 20 to 40° C. to obtain a photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance.

8. The method for preparing the photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 6, characterized in that: In step S1, the molar ratio of the diisocyanate monomer to the hydroxyl-containing acrylic acid derivative is 1:(1-1.3); In step S2, the molar ratio of the alcoholic hydroxyl group in the heterocyclic compound containing a urea bond to the intermediate product 1 is (0.8-1):

1.

9. The method for preparing the photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance as claimed in claim 7, characterized in that: The mass ratio of the photocurable acrylate to the diluent is 1:(0.65-0.9).

10. The method for preparing the photovoltaic adhesive with high adhesion, moisture resistance, heat resistance and yellowing resistance according to claim 7, characterized in that: The first and second catalysts are respectively selected from one or more of organic tin, organic bismuth, organic zinc, organic cobalt and organic base catalysts.

Citation Information

Patent Citations

  • High-thixotropy high-temperature-resistant yellowing-resistant photovoltaic solder strip UV adhesive, preparation method and sizing method

    CN117384580A

  • Urea (METH) acrylates or urea-urethane (METH) acrylates oligomers, compositions comprising the same, and uses thereof

    CN118510823A

  • Tacky adhesive composition curable with actinic energy ray and tape

    JP1994145607A

  • Adhesive, and connected structure of circuit material

    JP2009074027A

  • Active energy ray curable adhesive composition excellent in insulation property

    JP2017066322A